Hydrogen Isotope Composition of a Large Silicic Magma Reservoir Preserved in Quartz‐Hosted Glass Inclusions of the Bishop Tuff Plinian Eruption - Kenneth S. Befus; Kristina J. Walowski; Richard L. Hervig; Jeffrey T. Cullen (Geochemistry, Geophysics, Geosystems, 2020)
Abstract Water controls magmatic crystallization and drives volcanic eruptions, but little is known about its primary source in silicic systems. The hydrogen isotope composition of volcanic products provides a metric that can track and identify magmatic source, fractionation, or degassing processes. Despite such promise, hydrogen isotope measurements have never previously been acquired for undegassed silicic melt. To explore whether hydrogen isotopes can identify the source and modification of water in a silicic magma reservoir, we analyzed D/H ratios and dissolved H2O content of quartz‐hosted, rhyolitic glass inclusions from the early Bishop Tuff, a time‐honored testing ground for innovative petrologic studies. The rhyolitic inclusions indicate the early Bishop reservoir had δD values ranging from −40‰ to −60‰ (Vienna Standard Mean Ocean Water). The measured hydrogen isotope ratios do not follow systematic trends that would be predicted for open‐system degassing, rehydration, or diffusive loss. Observed isotopic variability in the microanalyses is instead attributed to analytical artifacts. The large silicic reservoir degassed as a closed system, resulting in limited fractionation obscured by the uncertainty of the measurements. Significant modification of melt D/H ratios by assimilation and fractional crystallization are unlikely, as their projected contributions are not observed. Dynamic geologic processes are thus not recorded by the hydrogen isotope composition of the inclusions. Instead, the rhyolitic melt represents a distinct, largely homogenous isotopic reservoir. When compared to the global record of basaltic glass inclusions, the rhyolitic inclusions preserve an isotopic signature that is most similar to subduction‐related mafic melts.